Increased Macrolide Resistance Rate of M3562 Mycoplasma pneumoniae Correlated With Macrolide Usage and Genotype Shifting - Wang, Yacui; Xu, Baoping; Wu, Xirong; Yin, Qingqin; Wang, Yi; Li, Jieqiong; Jiao, Weiwei; Quan, Shuting; Sun, Lin; Wang, Yonghong; Shen, Adong (Frontiers in Cellular and Infection Microbiology, 2021)
To characterize Mycoplasma pneumoniae (MP) strains and to clarify the continuous high rates of macrolide resistance, 1,524 oropharyngeal swabs collected from children in Beijing Children’s Hospital infected with MP during 2016-2019 were analyzed. Among the 1,524 samples, 1,386 harbored mutations associated with macrolide resistance; 1,049 samples were successfully classified into 11 genotypes using multiple locus variable-number tandem-repeat analysis (MLVA). The proportion of the predominant type, M4572, decreased from 84.49 to 70.77% over the time period examined, while that of M3562 increased from 11.63 to 24.67%. Notably, we also found that the frequency of macrolide resistance in M3562 drastically increased, from 60% in 2016 to 93.48% in 2019. Clinical data suggested that the frequency of resistant M3562 was higher in the macrolide usage group than in the nondrug usage group (90.73 vs 53.57%, P<0.0001), while the resistance rate of M4572 was not substantially affected by previous macrolide exposure. These findings validated that antimicrobial application and clonal expansion of resistant MP strains play important roles in the high rates of macrolide resistance.